Modelling and simulation of a low speed passenger car collision. (4th August 2014) - Johnson, W.R.; Baughn, T.V.; Johnson, D.B.
The development of a model for predicting passenger car response to low speed collisions with a test pendulum or a barrier is described. The collision scenarios are set forth in Federal Motor Vehicle Safety Standard (FMVSS) 215, Part 581. It was developed to provide an efficient tool for use in bumper design evaluation for compliance with FMVSS 215, Part 581, which requires that vehicle bumpers prevent damage 10 surrounding vehicle safety components in low speed (4.0 kph; 2.5 mph) collisions. The six degrees of freedom model utilises vehicle and bumper data including properties of energy absorbing devices common to modern passenger car bumper systems. The simulation code (BUMPER) is written in FORTRAN. It produces time histories of each of the generalised coordinates and of their first and second time derivatives, as well as of the magnitudes of the bumper absorber and impact forces. These simulation results can then be used in a subsequent bumper survivability analysis.